A Critical Review of “An Overview of Philosophy of Science” - Yassaman Hoshyar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article is a critical review of the book “An Overview of the Philosophy of Science”. The importance of this lies in the fact that it is the first Persian book in this field. What we confront in the introduction increases its importance which says “This book can be used as a textbook or even self-study book”. In this review, first, the approach of this book to topics such as induction, methodologies, and realism as well as the weights which are given to each of them and their clarity and ambiguity will be surveyed. Then, some further notes like what is necessary for a textbook and what this book lacks, and  summary of each chapter and questions for further thinking will be noticed. Finally, a conclusion and evaluation of the book and its purposes will be presented.